Milk/colostrum exosomes: A nanoplatform advancing delivery of cancer therapeutics. (1st May 2023) - Wallen, Margaret; Aqil, Farrukh; Spencer, Wendy; Gupta, Ramesh C.
Abstract: Chemotherapeutics continue to play a central role in the treatment of a wide variety of cancers. Conventional chemotherapy involving bolus intravenous doses results in severe side effects - in some cases life threatening - delayed toxicity and compromised quality-of-life. Attempts to deliver small drug molecules using liposomes, polymeric nanoparticles, micelles, lipid nanoparticles, etc. have produced limited nanoformulations for clinical use, presumably due to a lack of biocompatibility of the material, costs, toxicity, scalability, and/or lack of effective administration. Naturally occurring small extracellular vesicles, or exosomes, may offer a solution and a viable system for delivering cancer therapeutics. Combined with their inherent trafficking ability and versatility of cargo capacity, exosomes can be engineered to specifically target cancerous cells, thereby minimizing off-target effects, and increasing the efficacy of cancer therapeutics. Exosomal formulations have mitigated the toxic effects of several drugs in murine cancer models. In this article, we review studies related to exosomal delivery of both small molecules and biologics, including siRNA to inhibit specific gene expression, in the pursuit of effective cancer therapeutics. We focus primarily on bovine milk and colostrum exosomes as the cancer therapeutic delivery vehicles based on their high abundance, cost effectiveness, scalability, high drug loading, functionalization of exosomes for targeted delivery, and lack of toxicity. While bovine milk exosomes may provide a new platform for drug delivery, extensive comparison to other nanoformulations and evaluation of long-term toxicity will be required to fully realize its potential. Highlights: Exosomes, produced by most cells, play role in intracellular communication. Bovine milk and colostrum provide an abundant source of exosomes. Exosomes have been used to load small molecules for the treatment of cancer. siRNA can be loaded into or onto exosomes and delivered as a cancer therapeutics. Exosomes functionalized with targeting ligands can be used for tissue/organ targeting.